Sexual Harassment and Stigma Among the Youth in Kabale Municipality Kabale District. - Mugumya, Muhammadi (Kabale University, 2023)
The study examined sexual harassment and stigma among the youth in Kabale Municipality, Kabale District. The objectives of the study were; to identify the causes of sexual harassment and stigma among the youth, to examine the effect of sexual harassment and stigma among the youth, and to suggest strategies to curb sexual harassment and stigma among the youth. The study used a descriptive study design and a sample size of 50 respondents was used. The study findings on causes of sexual harassment and stigma among the youth were the nature of dressing, poverty, sexual coercion low-paying jobs, and sex discrimination. The study findings on the effect of sexual harassment and stigma among the youth were sexual harassment in childhood and adolescence is associated with dropping out of school and delinquency, it leads to loss of goodwill of the victim, sexual harassment leads to increased sexual arousal, sexual harassment affects the women economic self-sufficiency and it leads to distractions from work and job dissatisfaction. The study findings on strategies to curb sexual harassment and stigma among the youth were holding talks about sexual and reproductive rights, ensuring awareness of the youth on sexual harassment, the law should be put to use, the youth have to report the act of sexual harassment and youth empowerment to raise their self-esteem regarding their bodies. The study recommended that parents and guardians should cooperate and work hand in hand with the education authorities to bring the self-esteem of the youth, there should be establishment of organizations that work directly with the youth in teaching them their rights and the government should intervene by putting strict laws and to deal with whoever is found a victim of harassing the youth whether studying or not.